Linear morphometry and shell growth of the bivalve Tagelus plebeius as an indicator for salinity in Holocene South American estuaries - Addino, Mariana del Sol (2024)
Holocene sea-level fluctuations have resulted in the formation of coastal features like barriers, coastal lagoons, tidal flats and marshes in the Argentinean coast (SW Atlantic). Estuarine regressive deposits represent good multi-proxy archives for reconstructing past environmental conditions. Particularly, articulated shells of the stout razor clam Tagelus plebeius in life position are reliable indicators of palaeoestuarine characteristics in Buenos Aires province. The objective of this study was to cross-match shell morphometry and growth from modern and fossil T. plebeius, in order to infer freshwater and marine water influence in palaeoestuaries along the Buenos Aires province. The results showed higher freshwater influence in most Holocene sites, between around 8000 and 6000 a BP. This tendency seemed modified after the Middle Holocene allowing the development of coastal lagoons with intermediate salinity. By adding a new perspective from an indicator, i.e. morphometry and growth (sclerochronology) of an estuarine species, this salinity reconstruction reinforces the previous findings related to Holocene sea level fluctuations in the Argentine coast.